MR monitoring of minimally invasive delivery of mesenchymal stem cells into the porcine intervertebral disc. - Monika Barczewska; Joanna Wojtkiewicz; Aleksandra Habich; Miroslaw Janowski; Zbigniew Adamiak; Piotr Holak; Hubert Matyjasik; Jeff W M Bulte; Wojciech Maksymowicz; Piotr Walczak (PLoS ONE, 2013)
Bone marrow stem cell therapy is a new, attractive therapeutic approach for treatment of intervertebral disc (IVD) degeneration; however, leakage and backflow of transplanted cells into the structures surrounding the disc may lead to the formation of undesirable osteophytes. The purpose of this study was to develop a technique for minimally invasive and accurate delivery of stem cells.Porcine mesenchymal stem cells (MSCs) were labeled with superparamagnetic iron oxide nanoparticles (SPIO, Molday ION rhodamine) and first injected into the explanted swine lumbar IVD, followed by ex vivo 3T MRI. After having determined sufficient sensitivity, IVD degeneration was then induced in swine (n=3) by laser-evaporation. 3 x 10(6) SPIO-labeled cells embedded within hydrogel were injected in 2 doses using a transcutaneous cannula and an epidural anesthesia catheter. T2-weighted MR images were obtained at 3T before and immediately after cell infusion. Two weeks after injection, histological examination was performed for detection of transplanted cells.MSCs were efficiently labeled with Molday ION rhodamine. Cells could be readily detected in the injected vertebral tissue explants as distinct hypointensities with sufficient sensitivity. MR monitoring indicated that the MSCs were successfully delivered into the IVD in vivo, which was confirmed by iron-positive Prussian Blue staining of the tissue within the IVD.We have developed a technique for non-invasive monitoring of minimally invasive stem delivery into the IVD at 3T. By using a large animal model mimicking the anatomy of IVD in humans, the present results indicate that this procedure may be clinically feasible.